Cost Minimization Analysis of Oral Antidiabetic Drugs in Type II Diabetes Mellitus Patiens at Sultan Suriansyah Hospital January-December 2022 Period - Ain, Farah Noor; Aryzki, Saftia; Abdi, Muhammad Mahendra (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Diabetes According to WHO (2016) is a serious chronic disease that occurs when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin it produces. The high cost of treating DM patients is reaching USD 1,500 to 9,000 in developing countries. The difference in costs for oral antidiabetics and the high cost analysis method. This study aims to determine the minimum cost between metformin 500 mg and acarbose 100 mg drugs in Sultan Suriansyah Banjarmasin in adult patients. This research was conducted using a cross-sectional design based on medical records and detail of patient costs in January-December 2022. The number of sample in this study were 39 patients. The statistic analysis used in study is the Mann-Whitney test and the Independent T-Test. The result of the analysis of cost minimization based on the average total cost of therapy are Rp 419,560 for metformin 500ng and Rp 680,922 for acarbose 100 mg with a probability value > 0.05 for the cost of co morbidities which means that there is no significant difference between the two drugs. Probability value < 0.05 for antidiabetic oral drug costs, lab costs and total therapy costs which means the there is a significant difference between the two drugs. Conclusion in this study is aral antidiabetic therapy for minimal diabetes mellitus is metformin compared to acarbose.